PENGARUH POLITIK DALAM SISTEM PEMILIHAN KEPALA DAERAH DI INDONESIA - Asmuni - (Faculty of Law, University of Mataram, 2017)
The election of regional in Indonesia has not reached the objectives of the General Election as referred to in the Constitution 1945. This is much influenced by political parties, therefore the issue raised is the political influence in the system of regional elections. Based on the results of the discussion that analyzed and drawn conclusions: Political influence in the system of regional election in Indonesia has an important position (status) and role in every democratic system. The Party plays role very strategic liaison between government processes and citizens. Even the political parties that determine democracy, so it is a pillar that important to strengthened its institutionalization In any democratic political system (the degree of institutionalization). A good party system determines the functioning of the state administration system based on the principle of in a broad sense